Web-Based STT Wastukancana Library QR Code Presence Information System - Prasetio, Bayu; Jaelani, Irsan; Iskandar, Dadi; Saepul Malik, Akbar (RISTEC : Research in Information Systems and Technology, 2024)
In an era of increasingly complex technological advancements, digital transformation has penetrated all aspects of human life, including education. The use of QR code technology to record library attendance data on student ID cards is one of the most interesting innovations. Student ID cards, which used to be just tangible documents with names and pictures on them, have now developed into tools that utilize administrative convenience and the right technology. The use of QR code technology to record library attendance data is to make it easier for library staff to record STT Wastukancana library visitor data from manual to digital data. Extreme Programming is a software development method that aims to improve software quality and meet short development cycles, so that it is very responsive to changing user desires